An uncommon case of nonconvulsive status epilepticus successfully treated with enteral Brivaracetam: nonconvulsive status epilepticus successfully treated with Brivaracetam - De Liso, Alfredo; Ricci, Lorenzo; Bravi, Maria Cristina; Pezzella, Francesca Romana; Anticoli, Sabrina (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work. We present a case of a woman affected by nonconvulsive status epilepticus (NCSE) caused by cerebral hyperperfusion syndrome (CHS) after carotid endarterectomy (CEA) who was successfully treated with Brivaracetam (BRV) administered via nasogastric tube (NGT). Case Presentation. An 82-years old woman was referred for increasing blood pressure, severe headache and two focal motor seizures on postoperative day four after right CEA. CT scan showed edema of the right hemisphere with a midline shift of 5 mm. The patient underwent daily Electroencephalography (EEG) monitoring which showed continuous epileptiform discharges over the right hemisphere, compatible with a diagnosis of status epilepticus. She was treated with standard antiepileptic drugs (Phenytoin, Lacosamide and Levetiracetam iv) without clinical response. A therapeutic trial with BRV 200mg administered via nasogastric tube (NGT) was tried which resulted in substantial clinical benefit. Conclusions. The administration of new antiepileptic drugs (AEDs) such as BRV may result in significant clinical improvement in refractory cases of status epilepticus. The enteral administration of AEDs via NGT should always be considered for refractory cases of status epilepticus when standard iv treatment has failed or is not possible.